2017
DOI: 10.1002/lio2.71
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and improvement of sound quality in cochlear implant users

Abstract: ObjectivesCochlear implants (CIs) have successfully provided speech perception to individuals with sensorineural hearing loss. Recent research has focused on more challenging acoustic stimuli such as music and voice emotion. The purpose of this review is to evaluate and describe sound quality in CI users with the purposes of summarizing novel findings and crucial information about how CI users experience complex sounds.Data SourcesHere we review the existing literature on PubMed and Scopus to present what is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 78 publications
(140 reference statements)
0
32
0
5
Order By: Relevance
“…A bias toward unvoiced stops was found, a phenomenon that only occurred for the CI group and hence probably is implant related. This may be related to two main issues: (1) implants convey the F0 in voiced sounds rather poorly due to missing temporal information in the electrical signal for most implant models and to the electrode’s insertion depth possibly being too shallow to cover the whole cochlea (Hamzavi and Arnoldner, 2006; Svirsky et al, 2015; Caldwell et al, 2017) and (2) the VOT makes the unvoiced stops much easier to perceive than the voiced stops due to the aspirated pause between the stop and the following vowel in the VCV syllables.…”
Section: Discussionmentioning
confidence: 99%
“…A bias toward unvoiced stops was found, a phenomenon that only occurred for the CI group and hence probably is implant related. This may be related to two main issues: (1) implants convey the F0 in voiced sounds rather poorly due to missing temporal information in the electrical signal for most implant models and to the electrode’s insertion depth possibly being too shallow to cover the whole cochlea (Hamzavi and Arnoldner, 2006; Svirsky et al, 2015; Caldwell et al, 2017) and (2) the VOT makes the unvoiced stops much easier to perceive than the voiced stops due to the aspirated pause between the stop and the following vowel in the VCV syllables.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that perception of segmental rhythm in speech evolves from sensitivity to syllabic complexity to variation in consonant intervals and the amount of vocalic space with age. Children who are deprived of normal rhythmic development, such as prelingually deafened CI users, are notably deficient in the detection of voice emotion compared with their normal hearing counterparts . This observation highlights the unique albeit limited contribution of CIs (as opposed to vibrotactile stimulation) in providing gross temporal structure (e.g., sensitivity to the amplitude envelope) and sound quality appraisal (e.g., timbre and dynamic range) to its listeners.…”
Section: Rhythm Perception In Speechmentioning
confidence: 99%
“…Several studies show that PE stimulation implemented in a sound coding strategy to transmit low frequency information has a significant effect on sound quality (e.g. Munjal et al, 2015; Nogueira et al, 2015; Caldwell et al, 2017). Munjal et al (2015) found out that the use of PE stimulation when listening to music has a positive effect in the ability to detect alterations in low frequency or bass content in music.…”
Section: Discussionmentioning
confidence: 99%